Study and evaluation of CPU scheduling algorithms - González-Rodríguez, Miguel; Otero-Cerdeira, Lorena; González-Rufino, Encarnación; Rodríguez-Martínez, Francisco Javier (Heliyon, 2024)
In the teaching of the operating systems course, which is part of computer engineering degrees, a thorough understanding of processor scheduling algorithms is crucial. However, it has been identified that the current knowledge of classical algorithms is insufficient in the present context. Therefore, it is proposed to conduct a review of the state of the art in the field to identify new trends and algorithms that can enhance the teaching of the subject and improve student training. As a result, the state of the art is thoroughly reviewed, and study sheets are designed to facilitate the comprehension of the algorithms. Additionally, a software simulator is developed to compare different algorithms in a controlled environment, allowing for the validation of the most promising ones for classroom teaching. •Improved learning of process scheduling algorithms in computer engineering degrees.•Review of the state of the art regarding CPU scheduling algorithms.•Study sheets to facilitate learning and explanation of the algorithms.•Objective comparison of the performance results of different algorithms in an unbiased environment.